Pelatihan Pengolahan Data dan Pengukuran Topografi Jurusan Geologi Pertambangan SMK Negeri 4 Palangka Raya - Alvionyta, Agnes; Wardani, Riana Sri; Noveriady, Noveriady; Marsel, Marsel; Hairi, Adria; Gaol, Bintang B. T Lumban; Simamarta, Jhonatan G (Universitas Negeri Gorontalo, 2026)
This community service activity aimed to improve students’ competence in processing topographic survey data and understanding the utilization of measurement results in mining activities. The program was implemented at State Vocational High School 4 Palangka Raya involving students of the Mining Geology Department in grades twelve and thirteen. The implementation method used Service Learning combined with a participatory approach, which included material delivery, software-based data processing practice, map production, and evaluation through pre-test and post-test. The results showed a significant increase in students’ understanding and skills in processing topographic data, creating topographic maps, and interpreting measurement results for mining planning purposes. Participants were able to independently process field survey data using software and understand the importance of topographic information in mining activities. It can be concluded that the training program effectively improved students’ technical competence and readiness to face the demands of mining industry practices.